After Confucius Studies in Early Chinese Philosophy - Goldin, Paul R. (University of Hawai'i Press, 2005)
After Confucius is a collection of eight studies of Chinese philosophy from the time of Confucius to the formation of the empire in the second and third centuries B.C.E. As detailed in a masterful introduction, each essay serves as a concrete example of "thick description"-an approach invented by philosopher Gilbert Ryle-which aims to reveal the logic that informs an observable exchange among members of a community or society. To grasp the significance of such exchanges, it is necessary to investigate the networks of meaning on which they rely. Paul R. Goldin argues that the character of ancient Chinese philosophy can be appreciated only if we recognize the cultural codes underlying the circulation of ideas in that world. Thick description is the best preliminary method to determine how Chinese thinkers conceived of their own enterprise.